Agricultural trade policy and food security in the Caribbean : structural issues, multilateral negotiations and competitiveness - Deep Ford, J.R. (FAO RomeIT, 2007)
Discusses the structural features characterising the Caribbean countries, specifically the dynamic relationships between trade and food security. Focuses on multilateral trade negotiations, mainly those of the WTO; elaborates on the implications for Caribbean agricultural and food sector performance and policies; and introduces analytical tools for trade policy evaluation.